Risk Factors Associated with Diarrhea in Infants - Cahyani, Ariyani; Mulasari, Surahma Asti; Sukesi, Tri Wahyuni (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: Diarrhea is one of the leading causes of death among infants in Indonesia and is a significant public health issue. This study aims to identify and analyze various risk factors associated with diarrhea in infants through a literature review approach. Research Method: This study employed a literature review method with a content analysis approach, utilizing articles obtained from the PubMed, ScienceDirect, and Google Scholar databases. The keywords used are “Infants,” “Diarrhea,” and “Risk Factors.” Article selection was conducted systematically using the PRISMA framework, from identification through screening to eligibility assessment. Out of 208 articles obtained, 10 articles were selected that met the criteria for further analysis. Results and Discussion: The study's results indicate that factors closely associated with the incidence of diarrhea in infants include not being exclusively breastfed, poor personal hygiene among mothers, inadequate basic sanitation facilities at home, low maternal education, maternal employment status, and limited socioeconomic conditions within the family. These factors interact with each other and increase the risk of diarrhea in young children. Implications: These findings are significant for preventive efforts in public health, particularly in raising awareness and knowledge among parents about maintaining optimal hygiene, sanitation, and nutrition for their children.